The practice of birth preparedness and complication readiness (BPCR) in Panti District, Jember Regency - Devi Arine Kusumawardani; Ni'mal Baroya; Elok Permatasari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: High maternal mortality rates remain challenging in developing countries such as Indonesia. These maternal deaths are preventable with appropriate management and care. Birth preparedness and complication readiness (BPCR) is a crucial strategy for making prompt decisions to seek care resulting in reduced maternal mortality. Jember regency is one of the districts that rank first until the end of 2021 with the highest death rate in East Java and nationally.  Objectives: This study aims to assess the proportion of BPCR practices and the aspect of BPCR in pregnant women.Methods: This descriptive research was conducted among pregnant women in the working area of Panti Primary Health Service, Jember Regency as Primary Health Services with the highest maternal mortality rate in Jember regency in 2020. This study was conductedfrom August to November 2021. A total of 110 pregnant women were recruited by simple random sampling. The respondents were interviewed using the BPCR index, adapted from the John Hopkins Program for International Education in Gynecology and Obstetrics to identify nine indicators of BPCR.Results: The proportion of good BPCR in pregnant women was 60,00%. The most mentioned aspect of BPCR was planning transportation (89,10%) and planning to give birth with a skilled provider (82,7%). The elements that pregnant women are least prepared for are aware of the danger signs during pregnancy, childbirth, and postpartum.Conclusions: The proportion of good BPCR among pregnant women was moderate. Community-based health education about preparation for birth and awareness of danger signs during pregnancy, labor, and postpartum is crucial to prevent maternal mortality.